Screening of Biosurfactant Producers and Influence of Physicochemical Parameters on Its Production: An Overview - Anuradha Pendse; K. Aruna (Screening of Biosurfactant Producers and Influence of Physicochemical Parameters on Its Production: An Overview, 2021)
One of the consequences of increasing industrialization is the accumulation of hydrocarbon contaminants in the environment. A sustainable approach to overcome this adversity is to use biosurfactants as a tool for bioremediation. Besides, biosurfactants also show promising industrial applications in the field of food, detergents and crude oil recovery. The characteristic properties like low toxicity, action specificity, higher biodegradability and functionality at variable pH, temperature and salinity has increased the commercial value of biosurfactants. Also, biosurfactants are recommended as a substitute to chemical surfactants due to their low Critical Micelle Concentration (CMC). The CMC of biosurfactants is around 10–40 times lower than that of chemical surfactants. For these reasons, there is increasing interest in screening and isolation of new biosurfactant strains. The content in this book provides a complete overview of the advantages and disadvantages of different screening methods used for isolation of biosurfactant producers. In addition, the effect of various physicochemical parameters on optimization of biosurfactant production is also presented after a thorough review of literature available online.